(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The effect of freezing methods and diluents types on post-thaw sperm quality of Bangladeshi ram semen was studied. Two freezing methods and three diluents was tested as pooling effects (freezing methods or diluents) on post-thaw sperm parameters; sperm motility (SM), viability (SV), plasma membrane integrity (SPMI) and acrosome integrity (SAI), respectively. From selected ten rams, eight ejaculates were used for each freezing group (freezing methods × diluents). Semen samples were diluted by using two-steps for hand-made tris-based diluents (20% egg yolk): D1 (7% glycerol) and D2 (5% glycerol), and one-step dilution for commercial diluents: D3 (Triladyl®) at 35°C. After 4h of equilibration of temperature at 5°C, diluted semen samples was aspirated into 0.25 mL straws, and sealed. Straws were frozen in liquid nitrogen (LN2) vapour using two methods: F1 (manually in Styrofoam box, using three-steps method; +5°C to -80°C at -11.33°C/min, -80°C to -120°C at -26.66°C/min, and -120°C to -140°C at - 13.33°C/min) and F2 (programmable bio-freezer, using two-steps method; +5°C to -100°C at - 20°C/min and -100°C to -140°C at -10°C/min). Two semen straws from each batch were evaluated (37°C for 20 sec) for sperm parameters. In pool effects between freezing methods; SAI differed significantly (P < 0.001). The SM (56%) and SV (72%) were observed competitive. However, SPMI (67.58 ± 2.02%) and SAI (76.13 ± 1.42%) were higher in F1. Among diluents, SM (P < 0.006), SV (P < 0.008), SPMI (P < 0.012) and SAI (P < 0.019) differed significantly. The SM (61.25 ± 1.80%), SV (77.13 ± 1.47%), SPMI (68.31 ± 1.91%) and SAI (74.75 ± 1.64%) were highest in D3. In conclusion, the combination of manual freezing (three-steps) and handmade tris-based diluents (20% egg yolk, 5% glycerol) is suitable and sustainable method for cryopreservation of ram semen. Res. Agric., Livest. Fish.7(2): 235-241, August 2020